Knowledge of Pregnant Women regarding HIV/AIDS - Pandey, N (Journal of Chitwan Medical College, 2013)
A descriptive study was conducted with the purpose of assessing the knowledge of HIV/AIDS among the pregnant women in antenatal clinic of Bir Hospital, Kathmandu. Sixty pregnant women were selected using non- probability purposive sampling technique. A pretested Nepali version semi-structured interview schedule was used to collect the data from them. Ethical consideration was maintained throughout the study. The obtained data was analyzed using descriptive statistics. The data are presented in different tables. Findings related to socio-demographic characteristics revealed that half (50%) percent of the respondents belonged to the age of 20-24years. Majority (88.3%) of the respondents were literate and (85%) of them belonged to Hindu religion. Findings showed that (90%) of respondents have heard about HIV/AIDS. The most common sources of information of HIV/AIDS were Television (77.8%), Radio (75%) and newspapers (66.7%). Regarding transmission of HIV/AIDS, majority (88.9%) knew that HIV/AIDS is transmitted from sexual contact with infected person (81.5%) knew from infected blood transfusion and (70.4%) said from infected mother to child. More than (80%) of respondents said that commercial sex worker and having multiple sex workers were the high risk group for HIV/AIDS. Majority (77.8%) said by avoiding multiple sex partners and (72.2%) being faithful to the partner was the preventive measures of HIV/AIDS. Majority (61%) of respondents did not know the relationship between STI and HIV/AIDS. Majority (68.5%) of respondents did not know that there is available of drugs which lengthen the living years of life of people living with HIV/AIDS. Majority 51(98.1%) knew the use of condom is to prevent pregnancy, 44(84.6%) said prevent HIV/AIDS, 29(55.8%) said control STI. Although majority of the respondents had knowledge regarding the high risk group, mode of transmission and prevention of HIV/AIDS, some lacking areas has been identified that majority of the respondents were not aware about the the relationship between STI and HIV/AIDS. They also lacked awareness that use of condom controls STI and about availability of drug which prevents progression of HIV infection. On the basis of finding, it is concluded that health education and awareness programme should be planned to women attending the antenatal clinic to enhance their knowledge on HIV/AIDS prevention and management. DOI: http://dx.doi.org/10.3126/jcmc.v3i3.8632 Journal of Chitwan Medical College 2013; 3(3): 18-21